The Determinants of Revisit Intention and Recommendation Intention for Domestic Tourists - Nadia Ika Purnama; Yudi Siswadi; Siti Mujiatun; Jufrizen Jufrizen (International Journal of Business Economics (IJBE), 2023)
This study aims to examine and analyze the effect of destination image and tourist facilities on Revisit Intention and Recommendation Intention through Domestic Tourist Satisfaction at Lake Toba Tourism Destinations. The population in this study is domestic tourists. This study will be tested on tourists visiting tourist destinations on Lake Toba during the Covid-19 pandemic. The sample size in this study was calculated from the size of the indicator multiplied by 5 to 10. Because this study used 4 construct variables with a total of 55 indicators, the sample required in this study was at least 55 x 5 = 275, people. The types of data collected to support the variables studied are primary data and secondary data. Data collection techniques used were interviews, questionnaires, and documentation studies. The data analysis method used is the Structural Equation Model from the LISREL 8.80 statistical software package. The results of the study show that the image of tourist destinations and facilities has a significant positive effect on tourist satisfaction. Tourism facilities have a significant positive effect on Recommended Intention. Destination Image and Tourist Satisfaction have a significant positive effect on Revisit Intention. Tourist satisfaction has a positive effect on recommended intention significantly. Satisfaction can positively mediate the effect of Destination Image on Revisit Intention and tourist satisfaction can positively mediate the influence of tourist facilities on the Revisit Intention of Domestic Tourists at Lake Toba Tourism Destinations.